Factors related to help-seeking for cancer medical care among people living in rural areas: a scoping review - Oshiro, Mariko; Kamizato, Midori; Jahana, Sayuri (BMC health services research, 2022)
Despite the importance of timely diagnosis and access to treatment, previous studies have not adequately explored help-seeking behavior in cancer treatment among rural and remote residents. The barriers preventing help-seeking behavior also remain unclear. To address this research gap, this study conducted a scoping review to suggest a framework for eliminating barriers and facilitating help-seeking for cancer treatment among rural and remote residents. To conduct the scoping review, three English medical databases (PubMed, MEDLINE, and CINAHL) were examined for the keywords “rural,” “remote,” “cancer,” and “help-seeking.” The research objectives and study designs, participants, and excerpts describing help-seeking of the selected papers were recorded in a data charting form. Descriptions of help-seeking behavior were organized and summarized according to their meaning and integrated into factors using thematic analysis. All extracted factors related to help-seeking were sorted into four main themes according to the Ecological Model of Health Behavior, the theoretical lens for this scoping review: (1) Intrapersonal; (2) Interpersonal; (3) Groups, culture, and organizations; and (4) Policy/environment. Factors were categorized as barriers and facilitators of help-seeking. A total of 13 papers were analyzed. Intrapersonal factors such as self-reliance, symptom appraisal, and fatalism, were identified as barriers to help-seeking, whereas presentation of abnormal and serious symptoms facilitated help-seeking. Interpersonal factors such as lack of understanding of family members, influence of surrounding people, role obligations, and lack of trust in experts hindered help-seeking, whereas understanding from surrounding people such as family and friends, promoted help-seeking. Groups, cultural, and organizational factors such as prejudice, social stigma, shame, lack of anonymity, and social norms acted as barriers to help-seeking. Policy-related barriers to help-seeking included lack of medical services and physical distance from medical institutions, leading to a time burden. The study discussed the identified factors from a rural context. Future studies should consider the identified barriers and facilitators according to the four main themes in rural areas when formulating interventions to promote help-seeking. Our findings can offer a theoretical foundation to develop actionable policies, preventive strategies, and relevant interventional tools that may facilitate oncological service utilization in rural areas.